Molecular Cobalt Clusters as Precursors of Distinct Active Species in Electrochemical, Photochemical, and Photoelectrochemical Water Oxidation Reactions in Phosphate Electrolytes - Li, Xiaobo; Clatworthy, Edwin B.; Masters, Anthony F.; Maschmeyer, Thomas (Chemistry : a European journal, 2015)
Three cobalt model molecular compounds, Co‐cubane ([Co4(µ3‐O)4(µ‐OAc)4py4]), Co‐trimer ([Co3(μ3‐O)(µ‐OAc)6py3]PF6), and Co‐dimer ([Co2(μ‐OH)2(µ‐OAc)(OAc)2py4]PF6), are investigated as water oxidation reaction (WOR) catalysts, using electrochemical, photochemical, and photoelectrochemical methodologies in phosphate electrolyte. The actual species contributing to the catalytic activity observed in the WOR are derived from the transformation of these cobalt compounds. The catalytic activity observed is highly dependent on the initial compound structure and on the particular WOR methodology used. Co‐cubane shows no activity in the electrochemical WOR and negligible activity in the photochemical WOR, but is active in the photoelectrochemical WOR, in which it behaves as a precursor to catalytically active species. Co‐dimer also shows no activity in the electrochemical WOR, but behaves as a precursor to catalytically active species in both the photochemical and photoelectrochemical WOR experiments. Co‐trimer behaves as a precursor to catalytically active species in all three of the WOR methodologies. Cobalt catalysts: The cobalt species derived in situ from the three molecular cobalt compounds, Co‐cubane, Co‐trimer, and Co‐dimer, are found to be the actual catalytic species for the observed water oxidation activity in three water oxidation methodologies (electrochemical, photochemical, and photoelectrochemical). However, the ability to form active species from the cobalt precursors is highly dependent on their structure and the water oxidation reaction (WOR) protocols, as shown in the figure.